Flettner Rotor Implication on Ship Ferry The Kalianget-Kagean Route Using Computational Fluid Dynamics - Firdausyah, Akmal; Munazid, Ali; Pambudi, Prastyono Eko; Suwasono, Bagiyo (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Ship's Ferries are a sea crossing that continues to operate around the time. The consequence related to shipping activities is an increase in ship exhaust emissions. One alternative for ship propulsion that is environmentally friendly is the Flettner rotor. The working principle of the tool follows the theory of the Magnus effect, where the force arises due to the difference in pressure between the two sides of the Flettner rotor. This study implicates the Flettner rotor on the Kalianget-Kangean ferry route with variations in wind speeds of 10, 15 and 20 knots and variations in dimensions of 3x1, 5x1 and 7x1 meters with a rotational speed of 500 rpm. Optimal results through computational fluid dynamics (CFD) simulations show a coefficient of lift (CL) of 3.647 and a lift force (Fl) of 2,980,631.2 kilonewton with dimensions of 5x1 meters and a wind speed of 15 knots. While the implicit percentage of Flettner rotors in KMP. DBS I of 18.11%, KMP. DBS III of 11.27%, and KMP. NS 92 of 5.45%.